Financial Behaviour and Financial Literacy on Traders in Border Areas of Indonesia - Ayu Fridayani, J; Damas Sadewo, Y (KnE Social Sciences, 2018)
The purpose of this study is to understand the financial behavior and the level of financial literacy at traders in one of the border areas of Indonesia, namely Bengkayang, West Kalimantan. The majority of previous studies examined the financial behavior of investors in the stock market. It raises the motivation to know the financial behavior of the general merchants, even the pedagogues in the border areas that are associated with their level of understanding in managing finances. The border area becomes an interesting object to be studied because of the government’s commitment to build Indonesia from the periphery. By using approach and method of phenomenology research, it is concluded that (1) traders do not have written and systematic financial report that reflect daily income and expense, (2) traders have no commitment to save, (3) trader has negative habit in spending money, (4) the investment for future needs is not a priority, and (5) the limitations of knowledge, lifestyle, and the attitude of not wanting to develop is a factor supporting the formation of bad financial behavior patterns and low level of financial literacy. Various situations that describe the financial behavior and financial literacy are overcome with the role of government and private parties in creating synergies to increase public awareness. With continuous counseling and the availability of financial products that are internalized, good financial behavior and understanding of financial management can be realized. Keywords: financial behavior, financial literacy, traders, border areas